The Effectiveness of Wordwall Online Games as Technology-Based Learning on Grammar Quality among Junior High Students - Anisah Rosydiyah; Slamet Asari; Nirwanto Maruf (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In accordance with 21st century learning, conventional learning methods become unattractive and result in poor student participation in class. Wordwall online games are used as a tool to improve the quality of grammar in the ESL class. Using Wordwall online games in this study aims to determine the effectiveness and perceptions of Wordwall Online Games as Technology – Based Learning among junior high school students in learning grammar. This study administers quasi experimental design. The accessible population of this study was the students of class 7A and 7B of MTs Ma;arif Sidomukti in 2021/2022 academic year. The experimental class was class 4A which consisted of 30 students while the control class was class 30 which also consisted of 30 students. The experimental class was accompanied with Wordwall online games and the other was control class without Wordwall online games. The research instruments used to collect the data in this study was grammar multiple-choice test. The Data analysed using independent sample t-test with SPSS version 25. The result shows that probability value of both groups is 0.002 meaning that the probability value is higher than the level of significance 0.05 (0.002 < 0.05). It indicates that Wordwall online games significantly influence students’ grammar quality.